2015
DOI: 10.1371/journal.pone.0137198
|View full text |Cite
|
Sign up to set email alerts
|

Native and Non-Native Supergeneralist Bee Species Have Different Effects on Plant-Bee Networks

Abstract: Supergeneralists, defined as species that interact with multiple groups of species in ecological networks, can act as important connectors of otherwise disconnected species subsets. In Brazil, there are two supergeneralist bees: the honeybee Apis mellifera, a non-native species, and Trigona spinipes, a native stingless bee. We compared the role of both species and the effect of geographic and local factors on networks by addressing three questions: 1) Do both species have similar abundance and interaction patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
3
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 69 publications
2
82
3
11
Order By: Relevance
“…3E) than most pollinators in the network. These results thus support the idea that A. mellifera tends to be a highly generalist pollinator species that contributes to network nestedness and acts both as a connector within its own module as well as between modules (Giannini et al, 2015;Santos et al, 2012).…”
Section: A Mellifera In Plant-pollinator Networksupporting
confidence: 77%
See 1 more Smart Citation
“…3E) than most pollinators in the network. These results thus support the idea that A. mellifera tends to be a highly generalist pollinator species that contributes to network nestedness and acts both as a connector within its own module as well as between modules (Giannini et al, 2015;Santos et al, 2012).…”
Section: A Mellifera In Plant-pollinator Networksupporting
confidence: 77%
“…However, network connectance was not affected by A. mellifera removal and authors did not find any correlation between network structure and the proportion of interactions made by A. mellifera in the networks. Giannini et al (2015) studied 21 plant-bee weighted interaction networks from different ecosystem types, also in Brazil. They found that A. mellifera generalism and mean interaction strength was correlated to nestedness and plant niche overlap in their networks.…”
Section: The Case Of Pollinatorsmentioning
confidence: 99%
“…We expect that generalist species may be able to shift part of their behavior or resource use when faced with a newly arrived species, in this case, a NIS. Eventually, the community will adjust to the presence of this NIS as has been observed for Apis mellifera in Brazilian bee communities (Giannini et al 2015).…”
Section: Discussionmentioning
confidence: 80%
“…Eventually, the community will adjust to the presence of this NIS as has been observed for Apis mellifera in Brazilian bee communities (Giannini et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Giannini et al [42] observed invasive super-generalist bee species in Brazil replacing native super-generalist species which can modify the interactions in networks. The non-native, super-generalist bee species invaded into the core of the networks rapidly.…”
Section: Mutualismmentioning
confidence: 99%